Bridging academia and water-related business through competence development: Evidence from a pan-European project. (10th January 2018) - Bikfalvi, Andrea; Marques, Pilar; Pérez-Cabaní, María-Luisa; Juandó Bosch, Josep; Rodriguez-Roda, Ignasi
Abstract: Higher Education Institutions are becoming increasingly more aware of the need to join forces to contribute to making societies more sustainable. Developing innovation capabilities is one of the ways that has been identified to contribute in this respect. Within organizations, building capacity for innovation is critical across all sectors. Given this situation, the present article describes and tests a knowledge alliance in the water sector. The alliance in question has been established between universities and companies with the aim of reducing the gap between graduate-acquired and employer-required competences, especially regarding innovation capabilities, by means of international internships. The article provides a theoretical foundation regarding the concern for sustainability in two ways: i) by proposing competence-based education and learning as a more sustainable model compared to traditional approaches and (ii) identifying competences required and practiced in water innovation projects as a means of building more sustainable companies and ultimately societies. The empirical evidence is taken from a pan-European project, AQUAdemia, which is being implemented in five countries and has resulted in 18 pilot internships. The main result consists in providing an international multi-stakeholder collaboration formula through which future workforces are better trained for business needs. The theoretical value of this article is its focus on the intersection of three aspects (education, innovation and the water sector), since previous research has only relied on single topic or dual approaches.